SAMBADENA Hyperpolarization of 13C‐Succinate in an MRI: Singlet‐Triplet Mixing Causes Polarization Loss. Issue 6 (4th June 2019) - Berner, Stephan; Schmidt, Andreas B.; Zimmermann, Mirko; Pravdivtsev, Andrey N.; Glöggler, Stefan; Hennig, Jürgen; von Elverfeldt, Dominik; Hövener, Jan‐Bernd
Abstract: The signal enhancement provided by the hyperpolarization of nuclear spins of biological molecules is a highly promising technique for diagnostic imaging. To date, most 13 C‐contrast agents had to be polarized in an extra, complex or cost intensive polarizer. Recently, the in situ hyperpolarization of a 13 C contrast agent to >20 % was demonstrated without a polarizer but within the bore of an MRI system. This approach addresses some of the challenges of MRI with hyperpolarized tracers, i. e. elevated cost, long production times, and loss of polarization during transfer to the detection site. Here, we demonstrate the first hyperpolarization of a biomolecule in aqueous solution in the bore of an MRI at field strength of 7 T within seconds. The 13 C nucleus of 1‐ 13 C, 2, 3‐ 2 H2 ‐succinate was polarized to 11 % corresponding to a signal enhancement of approximately 18.000. Interesting effects during the process of the hydrogenation reaction which lead to a significant loss of polarization have been observed. Abstract : Like spinning plates : The first hyperpolarization of a biomolecule in aqueous solution in the bore of an MRI at field strength of 7 T within seconds has been reported. The 13 C nucleus of 1‐ 13 C, 2, 3‐ 2 H2 ‐succinate was polarized to 11 % corresponding to a signal enhancement of approximately 18.000.